Pendayagunaan Limbah Gula Aren di Desa Mongiilo sebagai Sumber Pupuk Organik Ramah Lingkungan - Musa, Weny J.A.; Duengo, Suleman; Arviani, Arviani; Kilo, Ahmad Kadir (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program focuses on utilizing domestic waste from the sugar palm craftsmen in Desa Mongiilo to create organic fertilizer. The project aimed to address the underutilization of organic waste from sugar palm production by converting it into a valuable agricultural input. The initiative involved training local farmers in organic farming methods, including the production of organic fertilizers using sugar palm waste. The results of this program showed significant improvements in soil fertility and plant health, thereby enhancing agricultural productivity in the village. This program has the potential to be a sustainable solution for waste management and agricultural enhancement in rural areas.